Globalization and urban culture in Dhaka - Abusaleh, Kazi; Rezaul Islam, M.; Nurul Islam, Md. (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book examines globalization and urban cultures in Dhaka, the capital of Bangladesh, from a socio-cultural view. It focuses on the evolving nature of urbanity in the city due to globalization and the global flow of information while framing the changing patterns of everyday cultures and practices. The volume explores key linkages and factors in urban transformation: the history and heritage of Old Dhaka; globalization, diverse urban cultures and ethnic spaces; changes in food habits, clothing, health practices and recreation; changing forms of festivals, marriages and religious practices; situation of indigenous people in Old Dhaka; and the role played by NGOs, civil society and the local government. With its rich ethnographic case studies and field-based evidence, it discusses the relations between technology-driven economic activities and increasing cultural homogenization. It traces developments induced by cultural globalization and includes contemporary debates along with comparisons of Asian and global perspectives. This book will be a useful resource for scholars and researchers of urban studies, city studies, urban sociology, social anthropology, cultural anthropology, political sociology, development studies, South Asian studies and cultural studies, and to those interested in Bangladesh"--
Keywords: Urbanization -- Bangladesh -- Dhaka; Social change -- Bangladesh -- Dhaka; Globalization -- Bangladesh -- Dhaka; Dhaka (Bangladesh) -- Social conditions; SOCIAL SCIENCE / Sociology / Urban; SOCIAL SCIENCE / Sociology / General; SOCIAL SCIENCE / General